Variations in soft facial tissue by using the interocclusal stabilization splint: 3d stereophotogrammetry - da Silva, Ana Maria Bettoni Rodrigues; Magri, Laís Valencise; Junqueira Júnior, Álvaro Augusto; Cazal, Mateus Sgobi; da Silva, Marco Antônio Moreira Rodrigues (Brazilian Dental Science, 2015)
Objective: To analyze variations in soft facial tissue by using the interocclusal stabilization splint (ISS) through the 3D stereophotogrammetry technique in a group of young women with temporomandibular disorder (TMD). Material and Methods: 20 females between 20 and 60 years of age (39.3 ± 12.5) and TMD diagnosis based on the criteria of the RDC/TMD, received treatment with ISS. Reference points were marked on the face and photos were performed twice using the Vectra (M3–Canfield®): with and without ISS. In the 3D images the following variables were measured: area of the cheeks and lips (cm3), linear labial distances (Ls-Cph, Cph-Ch, Li-Ch, Ls-Li, Ch-Ch), lower third of the face (Sn-Me), height of the upper lip (Sn-Ls)/lower (Li-Me) and the angles C-Sn-Ls, N-Sn-Pg and Li-Sl-Pg. The data were analyzed in a descriptive manner, the times with and without ISS were compared using the t-test and the Pearson's correlation was employed in order to correlate the ISS thickness with the facial measurements (5% significance). Results: A statistically significant difference was found only for the variables of the lip area (p= 0.01) and Ls-Li (p=0.006) in comparison with/without ISS. No correlation was found between the ISS thickness and the lip area for both face sides, right (p=0.7; r=0.07) and left (p=0.9; r=-0.001). Conclusions: The use of interocclusal stabilization splint does not provide large changes in facial morphology, with the exception of the lip area and height.